Aryl Hydrocarbon Receptor-Dependent Metabolism Plays a Significant Role in Estrogen-Like Effects of Polycyclic Aromatic Hydrocarbons on Cell Proliferation. (22nd June 2018) - Hýžd′alová, Martina; Pivnička, Jakub; Zapletal, Ondřej; Vázquez-Gómez, Gerardo; Matthews, Jason; Neča, Jiří; Pěnčíková, Kateřina; Machala, Miroslav; Vondráček, Jan
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread environmental contaminants that interact in a complex manner with both the aryl hydrocarbon receptor (AhR) and estrogen receptors (ER). Their potential endocrine-disrupting activities may depend on both inhibitory AhR-ER cross-talk and on AhR-dependent metabolic production of estrogenic PAH metabolites. Here, we analyzed the impact of AhR on estrogen-like effects of PAHs, such as benzo[ a ]pyrene (BaP), in particular, on control of cell cycle progression/cell proliferation. Using AhR knockout variant of estrogen-sensitive human breast cancer MCF-7 cells (MCF-7 AhR KO cells), we observed that the AhR-dependent control of cytochrome P450 family 1 (CYP1) expression played a major role in formation of estrogenic BaP metabolites, most notably 3-OH-BaP, which contributed to the ER-dependent induction of cell cycle progression/cell proliferation. Both BaP metabolism and the BaP-induced S-phase transition/cell proliferation were inhibited in MCF-7 AhR KO cells, whereas these cells remained sensitive towards both endogenous estrogen 17β-estradiol or hydroxylated BaP metabolites. BaP was found to increase the activity of ER-dependent luciferase reporter gene in wild-type MCF-7 cells; however, unlike its hydroxylated metabolite, BaP failed to stimulate luciferase activity in MCF-7 AhR KO cells. Similarly, estrogen-like effects of other known estrogenic PAHs, such as benz[ a ]anthracene or 3-methylcholanthrene, were diminished in MCF-7 AhR KO cells. Ectopic expression of human CYP1A1 and CYP1B1 enzymes partly restored both BaP metabolism and its effects on cell proliferation. Taken together, our data suggest that the AhR-dependent metabolism of PAHs contributes significantly to the impact of PAHs on cell proliferation in estrogen-sensitive cells.